(untitled) (المجلة العراقية للعلوم الاقتصادية, 2025)
The research initially defines the green economy and shows the importance of this type of economy in its relation to renewable energy. Then it presents and analyzes successful Western experiences of the green economy and renewable energy policy, as well as green economy and renewable energy initiatives in Asia, Africa, Latin America and Oceania. The research concludes its axes by presenting and discussing models of green economy and renewable energy initiatives in the Arab world.